PTH-135 Gastroenterology in situ simulation: the ASPIH guidance in practice. (8th June 2018) - Jackson, Louisa; Suggitt, Debbie; Baxter, David; Jafar, Wisam
Abstract : Introduction: Simulation is a powerful tool for learning, and has been shown to be effective for a wide range of skills. In situ simulation is delivered in the clinical setting with the objective of incorporating simulated learning into real working environments. This provides additional scope for learning, not only team working and clinical skills, but also in identifying latent errors. We established an in situ simulation programme within our gastroenterology department using the recent Association for Simulated Practice in Healthcare (ASPiH)¹ key standards: clearly defined learning objectives, authentic delivery and faculty proficient in simulation-based education. Methods: We identified key learning objectives, highlighting both human factors (at an individual, team and organisational level) and clinical teaching pertinent to the gastroenterology team, to cover over the programme. We incorporated this into a series of clinically relevant scenarios including massive upper gastrointestinal haemorrhage, biliary sepsis and post-ERCP complications. We ran five sessions over a six month period with three faculty, involving twenty four participants across the spectrum of the multi-disciplinary team (MDT). Following each in situ simulation, we facilitated a short, structured debrief session highlighting key learning points, providing feedback and enabling reflection. Results: Twenty three of twenty four participants enjoyed the sessions and felt better prepared for similar real life clinical scenarios. All team members involved felt well supported during the debrief process. Through our sessions we recognised both latent error (confusion over the new massive haemorrhage protocol contact number) and resource requirements (no Sengstaken–Blakemore tube on the ward). Following the sessions we highlighted specific teaching needs, and established a mandatory teaching day for our Junior and Senior Clinical Fellows, focusing on the management of the acutely unwell adult. Conclusions: In conclusion, in situ simulation has proved a useful modality to deliver teaching in the clinical setting. The response from the multi-disciplinary team has been overwhelmingly positive, especially with feedback reporting it improved team dynamics. The team is currently expanding the in situ simulation programme across other wards to provide ongoing simulation teaching and consequently improve patient safety. Reference: . SIMULATION-BASED EDUCATION IN HEALTHCARE– STANDARDS FRAMEWORK AND GUIDANCE. (2016). 1st ed. Health Education England. Available at: http://aspih.org.uk/wp-content/uploads/2017/07/standards-framework.pdf [Accessed 8 Feb. 2018].